Inovasi Pelayanan Administrasi Nikah Terintegrasi di Kantor Urusan Agama Kecamatan Enam Lingkung Kabupaten Padang Pariaman - Nugi Alindro; Kusdarini Kusdarini; Roni Ekha Putera (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2021)
Purpose of this study to describe the Integrated Marriage Administration Service Innovation (PANTER) by KUA Kecamatan Enam Lingkung, Padang Pariaman. Public service innovation doesn’t not require a something new, but can be a new approach in contextual at the sense that innovation not limited from there are ideas and practicies of innovation but can be in the form of innovation resulting from expansion or quality improvement of existing innovations. This research is using descriptive approach by qualitative methods. Technique of collecting the data was by interview and documentation.This study is motivated by good will from Head of KUA Kecamatan Enam Lingkung to make easier community of Enam Lingkung District to get some documents and to assist Disduckcapil Kabupaten Padang Pariaman in orderly administration. The result of this study is PANTER helped community to obtaining marriage documents and population documents like Nationality ID, Family Register, and Nationality Health Insurance without spending money and time. However, there are still some problem faced by the community and PANTER officer, such as lack of facilities and infrastructure, lack of PANTER officer and unstable internet networks.